Mieux comprendre la situation de travail d’aide aux devoirs pour faciliter le développement professionnel des acteurs du périscolaire en formation - Marc Daguzon; Évald Maillet; Sylvie Cèbe; Sylvie Moussay (Recherches en Éducation)
The implementation of the reform of school paces has revealed the difficulties experienced by actors who have difficulties working in structures outside school time. Between turnover, precariousness and lack of professional recognition, these actors relate situations of thwarted or prevented work. With reference to the professional didactic approach, this study aims to identify the knowledge used by these actors involved in the homework assistance situation. The differences observed between the situations experienced and the desired situations make it possible to identify the potential for the development of the actors operational models, which originates in the knowledge in action resulting from the professional type of animation. The mobilization of this knowledge in training is an issue for the professional development of extracurricular actors in the homework assistance situation.